Activation of the angiotensin II receptor promotes autophagy in renal proximal tubular cells and affords protection from ischemia/reperfusion injury - Hirohito Sugawara; Norihito Moniwa; Atsushi Kuno; Wataru Ohwada; Arata Osanami; Satoru Shibata; Yukishige Kimura; Koki Abe; Yufu Gocho; Masaya Tanno; Tetsuji Miura (Elsevier, 2021)
Roles of the renin-angiotensin system in autophagy and ischemia/reperfusion (I/R) injury in the kidney have not been fully characterized. Here we examined the hypothesis that modest activation of the angiotensin II (Ang II) receptor upregulates autophagy and increases renal tolerance to I/R injury. Sprague-Dawley rats were assigned to treatment with a vehicle or a non-pressor dose of Ang II (200 ng/kg/min) for 72 h before 30-min renal I/R. LC3-immunohistochemistry showed that Ang II treatment increased autophagosomes in proximal tubular cells by 2.7 fold. In Ang II-pretreated rats, autophagosomes were increased by 2.5 fold compared to those in vehicle-treated rats at 4 h after I/R, when phosphorylation of Akt and S6 was suppressed and ULK1-Ser555 phosphorylation was increased. Serum creatinine and urea nitrogen levels, incidence of oliguria, and histological score of tubular necrosis at 24 h after I/R were attenuated by Ang II-pretreatment. In NRK-52E cells, Ang II induced LC3-II upregulation, which was inhibited by losartan but not by A779. The results indicate that a non-pressor dose of Ang-II promotes autophagy via ULK1-mediated signaling in renal tubular cells and attenuates renal I/R injury. The AT1 receptor, but not the Mas receptor, contributes to Ang-II-induced autophagy and presumably also to the renoprotection.